Pemberdayaan Masyarakat Desa: Studi Kasus di Desa Rasau Jaya Satu Universitas Panca Bhakti Pontianak Tahun 2025 - Arweni Arweni; Oktavia Triyani; Wawan Kristanto; Ernanda Laura Herben; Andi Kristandi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
Community Service Program (KKN) is a student service activity aimed at applying the knowledge and skills acquired during college to real community problems. This KKN was conducted in Desa Rasau Jaya Satu, Kecamatan Rasau Jaya, Kabupaten Kubu Raya for a duration of four weeks in August 2025. The program involved comprehensive activities, including identifying key village issues and potentials, as well as implementing various development programs focused on improving infrastructure, education, agricultural productivity, and environmental cleanliness. The methods used during this KKN included direct observation, in-depth interviews with community leaders and members, community counseling sessions, and active participation of local residents in all stages of the program. As a result, students successfully accomplished multiple work programs such as the creation and installation of street name signs and cemetery markers, socialization campaigns addressing bullying prevention and environmental awareness, and technical assistance in resident data input for better governance. These efforts collectively contributed to positive impacts on the social, educational, environmental, institutional, and economic conditions of Desa Rasau Jaya Satu. Furthermore, this KKN has enhanced the awareness and sensitivity of participating students regarding the importance of community engagement and empowerment, as well as reinforced their practical skills in interdisciplinary collaboration. The integrated approach of this program supports sustainable village development and exemplifies the role of higher education institutions in fostering community welfare and student personal growth.